2004
DOI: 10.1177/001789690406300303
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to healthier eating in a disadvantaged community

Abstract: Objective The research objective was to identify how healthy eating was understood in a disadvantaged community and how barriers to healthy eating might be overcome. Design Participatory action research. Setting Communities in Gurnos, Merthyr Tydfil, one of the most deprived areas in the UK.Method Trainees on a participative methods course undertook handson research, directed by the course leader and local researchers. Respondents were from established local groups, including elderly, carer and toddler and res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 6 publications
1
23
0
Order By: Relevance
“…The results of other studies have shown that obesity is increasing (NPHSW, 2007) and the public is being 'bombarded with advice from various sources offering quick fix cures or the latest fad diets' (British Dietetic Association, 2008). Food choice is also influenced by the meanings that food holds such as conception of self and acceptance within a community (O'Neill, 2004). The aims of the first phase of this project were to conduct exploratory interviews, to formulate ideas, and begin to gain an understanding of some of the issues and language that individuals feel are important in terms of their diet (Oppenheim, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The results of other studies have shown that obesity is increasing (NPHSW, 2007) and the public is being 'bombarded with advice from various sources offering quick fix cures or the latest fad diets' (British Dietetic Association, 2008). Food choice is also influenced by the meanings that food holds such as conception of self and acceptance within a community (O'Neill, 2004). The aims of the first phase of this project were to conduct exploratory interviews, to formulate ideas, and begin to gain an understanding of some of the issues and language that individuals feel are important in terms of their diet (Oppenheim, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The eatwell week resource needs to increase emphasis on the role of carbohydrates in a healthy diet. Inconsistent advice from health professionals is cited by the public as a barrier to healthy eating and the present work has highlighted the need for ongoing nutrition training and education of health professionals (5,10,11) . Lack of time has been frequently cited as a barrier to healthy eating (5,10,11) .…”
Section: Discussionmentioning
confidence: 96%
“…Inconsistent advice from health professionals is cited by the public as a barrier to healthy eating and the present work has highlighted the need for ongoing nutrition training and education of health professionals (5,10,11) . Lack of time has been frequently cited as a barrier to healthy eating (5,10,11) . The breakfasts and lunches included in the eatwell week were intended to be simple, easily prepared meals with minimal difficulty and time required for preparation.…”
Section: Discussionmentioning
confidence: 96%
“…Pakistan shares a major burden of parasitic, infectious and communicable diseases. These diseases can be overcome with prevention and health promotion measures rather than large investments on treatment and medicines (O'Neill et al, 2004;Prasla and Prasla, 2011). These measures, however, require positive health seeking behaviors, which Pakistani society lacks (Shaikh and Hatcher, 2004).…”
Section: Poor Behavior and Lack Of Understanding In Community Towardsmentioning
confidence: 99%